ChemInform Abstract: Microwave‐Assisted Synthesis of Functionalized Spirohydantoins as 3‐D Privileged Fragments for Scouting the Chemical Space. Issue 42 (September 2016) - Prevet, Hugues; Flipo, Marion; Roussel, Pascal; Deprez, Benoit; Willand, Nicolas
Abstract: A wide variety of spirohydantoins are prepared via microwave‐assisted reactions of cyclic ketones with KCN and ammonium carbonate.